Vertical and horizontal push tests on specimens with a Trefoil decking profile. (February 2021) - Russell, Matthew J.; Clifton, G. Charles; Lim, James B.P.
Abstract: The vertical push test has historically been the primary means used to evaluate the strength of shear connectors used in steel-concrete composite floors; however, these tests can be difficult to conduct and generally their results have been shown to not well represent the behaviour of shear connectors in a full sized composite beam. This paper describes a series of twenty-four push tests on composite beam specimens with Trefoil profile steel decking and headed, through-deck welded shear connectors (shear studs) using two different test set-ups. Twelve push tests on specimens with 19 mm and 22 mm shear studs were conducted using the double sided vertically oriented setup from AS/NZS 2327 and Eurocode 4, with transverse load applied across the slab faces. Twelve further push tests were conducted on specimens with 19 mm diameter studs using a new horizontal set-up. The results of the vertical tests suggest that the equations in Eurocode 4 for the determination of design shear resistance may be unconservative for 19 mm and 22 mm shear studs in 80 mm deep Trefoil decking ribs. The horizontal test specimens showed the same poor post-peak load retention that is characteristic of push tests conducted using the vertical test set-up without the application of transverse load. These parallel test programs are an exploratory step towards understanding the differences in behaviour observed in vertical and horizontal push tests and are the initial efforts in a continuing research program to develop a horizontal push test that provides a close approximation of the behaviour observed in full-beam tests.